PROGRAM BIMBINGAN PRIBADI BERDASARKAN PROFIL KASIH SAYANG DIRI SISWA SMK : Studi Deskriptif terhadap Siswa Kelas XII SMKN 1 Cimahi Tahun Ajaran 2018/2019 - Hapsari Dwilarasati., - (2018)
Kasihsayangdiriadalahkemampuanseseoranguntukmemahamidiriataskegagalandankekurangandirisebagaipengalamanpadaumumnyasehinggatidakmenyalahkanbahkanmenghakimidirisendiri. Terdapatfenomenamengenairendahnyakasihsayangdiri yang dimilikisiswa. Penelitianbertujuanuntukmerumuskan program bimbinganpribadiberdasarkanprofilkasihsayangdirisiswa. Penelitianmenggunakanpendekatankuantitatifdenganmetodesurvei. Teknik pengumpulan data yang digunakandengan cara penyebaran angkettertutupdengan model likert.Penelitiandilakukankepada 606 siswakelas XII di SMK Negeri 1 CimahiTahunAjaran 2018/2019. Hasilpenelitianmenunjukkansecaraumumbahwakasihsayangdirisiswaberadapadakategorisedang yang berartisiswacukupmampumemahamidanmenerimakekurangansertakegagalandirinyadengankebaikandiri. Agar mencapaikategori yang tinggidiperlukan program bimbinganpribadiuntukmengembangkankasihsayangdirisiswa. Penelitianberhasilmerumuskan program bimbinganpribadiberdasarkanprofilkasihsayangdirisiswa yang telahterujikelayakannyamelaluijudgement program olehpakardanpraktisibimbingandankonseling;---Self-compassion is a person's ability to understand themselves for their failure and inadequate as experience in general so they do not blame and even judge themselves. There is a phenomenon regarding the low self-compassion of students. This study aims to formulate a personal guidance program based on the profile of student's self-compassion. The study uses a quantitative approach with survey methods. The data collection techniques are used by distributing closed questionnaire with a likert model. The study was conducted on 606 students of class XII in SMK Negeri 1 Cimahi Academic Year 2018/2019. The results of the study show in generally that the students' self-compassion are in the medium category, which means that students are sufficiently able to understand and accept their deficiencies and failures with goodness. In order to achieve a high category, a personal guidance program is needed to develop students' self-compassion. This study succeeded in formulating a personal guidance program based on the profile of students' self-compassion which has been tested for its feasibility through program judgment by experts and practitioners of guidance and counseling.